FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PADA PERUSAHAAN NONKEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - YENIATIE YENIATIE; NICKEN DESTRIANA (Jurnal Bisnis dan Akuntansi, 2010)
The purpose of this research is to analyze the effect of insider ownership, institutional ownership, dividend policy, asset structure, profitability, firm growth and business risk on debt policy. This research used for 45 non financial companies firms which listed in Indonesia Stock Exchange during 2005 until 2007. The result of research shows that institutional ownership, asset structure, profitability and firm growth have influence to debt policy. While insider ownership, dividend policy and business risk have not influence to debt policy